Legal Protection of Children After Divorce: A Comparative Study of Islamic Law and the Child Protection Act - Syafiq, Muhammad; Fitriyanti, Vivit; Harun, Nurlaila; Abidin, Kurniati; Haikal Tunisi, Muhammad; Stanislaus, Surip (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This article examines the legal protection of children after divorce through a comparative approach between Islamic law and the Indonesian Child Protection Act. Divorce often has negative consequences for children—psychologically, socially, and economically. Therefore, a legal framework is needed that can guarantee the comprehensive fulfillment of children’s rights, even after the termination of parental marital relations. From the perspective of Islamic law, the principle of child protection is rooted in the objectives of sharia (maqāṣid al-sharī‘ah), particularly in preserving life (ḥifẓ al-nafs), lineage (ḥifẓ al-nasl), and intellect (ḥifẓ al-‘aql). The concepts of ḥaḍānah (custody), the obligation of financial support, and the continuity of emotional roles of parents indicate that Islam places the welfare of the child as a top priority. Meanwhile, Law No. 35 of 2014 guarantees the rights of children after divorce through the principle of the best interest of the child, although its implementation still faces challenges such as weak legal enforcement and lack of supervision in the fulfillment of custody and child support. This article employs a normative-comparative research method and a maqāṣid-based analysis. The findings show the urgency of harmonizing the regulations between the two legal systems to realize a child protection framework that is just, comprehensive, and contextually relevant. The integration of maqāṣid principles into national policy is key to strengthening the child protection system in Indonesia.